Investigation of freeze-thaw performance for sustainable rubberized concrete composites with different water to cement ratios - Bulut, H. Alperen; Kandil, U. (Materiales de Construcción, 2025)
This research aimed to evaluate the freeze-thaw performance of waste rubber substituted concretes with two different water/cement ratios. Different ratios of waste rubber were used in concrete by substituting fine and coarse aggregates. The weight and compressive strength losses of rubberized concrete and control concretes subjected to freeze-thaw were experimentally examined. The changes in the microstructure of the concrete were analyzed by using a Scanning Electron Microscope (SEM). Furthermore, ANOVA was used to test the significance of the selected parameters statistically. The control concrete with a 0.5 water/cement ratio had eight times higher mass loss compared to the rubberized concrete. The SEM analysis results were consistent with the freeze-thaw test results. ANOVA that the waste rubber substitution ratio had a significant effect on the freeze-thaw performance of rubberized concrete. Water/cement ratio, together with the waste rubber substitution ratio, is an effective parameter on the freeze-thaw resistance of rubberized concrete.